Conceptualization of the metaphor of body parts lisanun ’tongue’ in the Koran: Cognitive semantic study - Fathurrohim, Ilham Hanif; Nur, Tajudin (Universitas Dian Nuswantoro, 2024)
This research aims to describe the conceptualization of the metaphor of body parts lisanun 'tongue' in the Koran. The Koran, as a guide for Muslims not only uses denotative language to convey meaning, but also figurative language, one of the variants of which is metaphor. Metaphors are basically not just words but involve the human cognitive side as well. Therefore, to understand the message in the Koran, a deep understanding of the conceptualization of metaphor is required. One of the things that is often used as a metaphorical expression is parts of the human body. Therefore, it is an object that is close to human life. This research is descriptive and qualitative in nature, with the Koran as the data source. Data were analyzed using conceptual meaning theory, according to Lakoff and Johnson. The results of the research show that the body part 'tongue' in the Koran is often used metaphorically to express several things, namely (1) the tongue as an action, which consists of the act of mocking, the act of lying, the act of accountability, the act of reading, the act of not being fluent in speaking, the act of speaking, the act of exchanging news, (2) the tongue as speech, and (3) the tongue as language.